Mentale und physische Gesundheit im Alter Der Einfluss von Armut, Einkommensungleichheit und Vermögensungleichheit - Franzese, Fabio (Verlag Barbara Budrich, 2020)
How do changes in the financial situation affect different dimensions of health in old age? In empirical analyzes using longitudinal data from the Survey of Health, Aging and Retirement in Europe (SHARE), the author examines various dimensions of health: depression, subjective health and physical limitations. The effects of income and wealth inequality in society on individual health are also being researched .; How is the financial situation of a person linked to their health in old age? Empirical analyzes using longitudinal data from the Survey of Health, Aging and Retirement in Europe (SHARE) examine various dimensions of health: depression, subjective health and physical limitations. In addition, the influences of income and wealth inequality in society on individual health are investigated.